Rooting linguistic psychology in the light of the Islamic heritage - Ali, Asem Shehadeh Saleh (International Journal of Latest Research in Engineering and Management, 2023)
Man is a speaking animal, and it means that man can translate his thoughts and feelings into words and speech that are understandable between people. The words and speech that are meant by language, which is a system of symbols and signs that ultimately constitute one of the tools of knowledge. Language and man cannot be separated between them. Language develops in the mind of a young person; he went through stages. In the origin of psychology and linguistics, there is something different, and then after that, scholars discuss it and reveal that he acquires language. As Allah Almighty said: {Surely, we have created man in the best form}, and by it Ibn Kathir said it means “This is what is sworn by, which is that Allah created man in the best form and erect shape, except for the most beautiful parts”. The person should memorize and benefit from this blessing well. The researcher will discuss how perception, memory and remembrance are related to language according to Muslim scholars and will reveal the relationship of language with learning. The research aims to define the topics of contemporary linguistics. A statement of the position of the ancients on the issues of psycholinguistics. Linguistic psychology was a large and well-known field in the West, and the researcher identifies this research from the opinion of Muslim scholars, especially Ibn Sina, Imam al-Ghazali, Ibn Majah, Ibn al-Jawzi, and others. The researcher identifies topics and issues presented by Muslim scholars on linguistic psychology.